Assembly language design and development for reconfigurable flexible assembly line. (April 2023) - Xiao, Leicai; Zeng, Long; Xu, Zhaobo; Liu, Xueping
Highlights: The concept of reconfigurable flexible assembly line in variable product. The methodology of design and develop the assembly language. Four-layer implementation architecture to integrate the hardware and software. Experiments in assembling the shuttle valve and relief valve. Abstract: To improve the efficiency and controllability of our previous proposed cross-category product assembly line, we design an assembly language (A-code) to express a product's assembly process. We further develop an IDE to describe assembly processes as statements, which are organized according to predefined syntax as an A-code file. The interpreter translates statements into executable low-level commands. In addition, a four-layer architecture of the A-code assembly system (ACAS) is proposed to implement this language, thus an A-code files can be run on the assembly line physically. The proposed ACAS can reconfigure each unit for specific products, and control their assembly processes. The expressivity of this language is validated in two assembly cases, a simple shuttle valve and a complex relief valve. The functionality and feasibility of this system are tested by assembling 50 relief valves. The results demonstrate our ACAS can perform complex assembly tasks in a more efficient way.